Blue carbon drawdown by restored mangrove forests improves with age. (15th March 2022) - Carnell, Paul E.; Palacios, Maria M.; Waryszak, Paweł; Trevathan-Tackett, Stacey M.; Masqué, Pere; Macreadie, Peter I.
Abstract: The restoration of blue carbon ecosystems, such as mangrove forests, is increasingly used as a management tool to mitigate climate change by removing and sequestering atmospheric carbon in the ground. However, estimates of carbon-offset potential are currently based on data from natural mangrove forests, potentially leading to overestimating the carbon-offset potential from restored mangroves. Here, in the first study of its kind, we utilise 210 Pb sediment age-dating techniques and greenhouse gas flux measures to estimate blue carbon additionality in restored mangrove forests, ranging from 13 to 35 years old. As expected, mangrove age had a significant effect on carbon additionality and carbon accretion rate, with the older mangrove stands (17 and 35 years old) holding double the total carbon stocks (aboveground + soil stocks; ∼115 tonnes C ha −1 ) and double the soil sequestration rates (∼3 tonnes C ha −1 yr −1 ) than the youngest mangrove stand (13 years old). Although soil carbon stocks increased with mangrove age, the aboveground plant stocks were highest in the 17-year-old stand. Mangrove age also had a significant effect on soil carbon fluxes, with the older mangroves (≥17 years) releasing one-fourth of the CH4 emissions, but double the CO2 flux compared to young stands. Our study suggests that the carbon sink capacity of restored mangrove forests increases with age, but stabilises once they mature (e.g., >17 years). This means that by using carbon sequestration and emissions from natural forests, mangrove restoration projects may be overestimating their carbon sequestration potential. Highlights: Soil age-dating revealed the carbon sequestered by restored mangrove forests. Older mangroves hold double the total carbon stocks (∼115 t C ha −1 ) than younger ones. Older mangroves have double the sequestration (∼3 t C ha −1 yr −1 ) than younger ones. Mangrove age is linked to low methane emissions, but high carbon dioxide fluxes. Managers must include mangrove age when predicting carbon offsets from restoration.